What do people include when they self-rate their health? Differential associations according to health status in community-dwelling older adults - Schüz, Benjamin; Wurm, Susanne; Schöllgen, Ina; Tesch-Römer, Clemens (Quality of life research, 2011)
Self-rated health (SRH) is widely regarded a valid and reliable indicator of health status. The validity of self-rated health has been demonstrated in many studies, for example by predicting mortality over and above medical and epidemiological data. However, the meaning of SRH can differ between individuals, especially in elderly individuals with considerable individual differences in their physical health states. It is thus important to determine whether predictors of self-rated health vary according to physical health status in order to interpret self-rated health data. In a representative survey study, 1174 individuals over 65 years of age rated their health and filled in questionnaires on subjective well-being, control beliefs, depressive symptoms, and functional health. Structural equation modeling with latent moderated structural equations was used to determine whether health status (number of illnesses) moderated the association of self-rated health with these predictors. Self-rated health was predicted by positive affect, depressive symptoms, control beliefs, and physical functioning. Moderated effects were found for positive affect and physical functioning, suggesting that there are stronger associations with positive affect in healthier individuals and stronger associations with physical functioning in less healthy individuals. This implies that SRH has differential associations depending on health status, which should be taken into account in interpreting any research with SRH as predictor or criterion. © 2011 Springer Science+Business Media B.V.
Keywords: Health status; Latent moderated structural equations; Older people; Self-rated health